Irkutsk Strength and Spirit Award - Lisitsina, Yana (project baikal, 2022)
Mark Meerovich's activities as a defender of Irkutsk’s wooden architectural heritage have made an invaluable contribution to the preservation of the city's historical appearance. The article describes the history, criteria and content of the Mark Meerovich Award. In 2021 the prize was first awarded to the architectural historian I. Kalinina for her research works on cultural heritage sites. Her publications are an example of thorough professional work.
Keywords: Irina Kalinina; Mark Merovich Award; Irkutsk; architectural heritage; scientific activity